Anti-quorum sensing activity, toxicity in zebrafish (Danio rerio) embryos and phytochemical characterization of Trapa natans leaf extracts. (10th August 2018) - Aleksic, Ivana; Ristivojevic, Petar; Pavic, Aleksandar; Radojević, Ivana; Čomić, Ljiljana R.; Vasiljevic, Branka; Opsenica, Dejan; Milojković-Opsenica, Dušanka; Senerovic, Lidija
Abstract: Ethnopharmacological relevance: Trapa natans L. (water chestnut or water caltrop) is a widespread aquatic plant, which has been cultivated for food and traditional medicine since ancient times. Pharmacological studies showed that water chestnut exhibits the wide range of biological activities, such as antimicrobial, antioxidative, analgesic, anti-inflammatory, as well as antiulcer. Aim of the study: Evaluation of anti-virulence potential and toxicity of T. natans methanol (TnM), acetone (TnA) and ethyl acetate (TnEA) leaf extracts. Materials and methods: The anti-quorum sensing activity of Tn extracts was addressed by measuring their effects on biofilm formation, swarming motility and pyocyanin and elastase production in Pseudomonas aeruginosa . Specific P. aeruginosa biosensors were used to identify which of the signaling pathways were affected. The lethal and developmental toxicity of extracts were addressed in vivo using the zebrafish ( Danio rerio ) model system. The phenolic composition of T. natans leafs extracts was analyzed by a linear ion trap-OrbiTrap hybrid mass spectrometer (LTQ OrbiTrapMS) and UHPLC system configured with a diode array detector (DAD) hyphenated with the triple quadrupole mass spectrometer. Results: Subinhibitory concentrations of Tn leaf extracts (0.2 MIC) inhibited pyocyanin and elastase production up to 50% and 60%, respectively, and reduced swarming zones, comparing to non-treated P. aeruginosa . TnA inhibited biofilm formation by 15%, TnM showed a stimulatory effect on biofilm formation up to 20%, while TnEA showed no effect. The bioactive concentrations of TnM and TnA were not toxic in the zebrafish model system. Twenty-two phenolic compounds were tentatively identified in TnM, where thirteen of them were identified in T. natans for the first time. Tn extracts, as well as their major components, ellagic and ferulic acids, demonstrated the ability to interfere with P. aeruginosa Las and PQS signaling pathways. Conclusions: This study demonstrates anti-virulence potential of Tn leaf extracts against medically important pathogen P. aeruginosa and confirms the ethnopharmacological application of this plant against microbial infections. Graphical abstract: